Implikasi Teknologi Informasi Komunikasi terhadap Prestasi Belajar Peserta Didik pada Kelompok Mata Pelajaran Agama - Sarton Abdullah; Arten Mobonggi; Najamuddin Petta Solong; Muh Arif (Pascasarjana IAIN Sultan Amai Gorontalo, 2019)
This article aims to reveal the implications of Information and Communication Technology on the learning achievement of students in the Religious Education subject group at Muhammadiyah High School in Gorontalo, using qualitative methods with a descriptive approach. The results showed that making ICT-based learning media with topics contained in the syllabus and lesson plans with due regard to the value of competency standards. The Qur'anic Hadith teacher and the history of Islamic culture have not used much but many motivate learning to students through material presentation. The implications of ICT on the learning achievements of fiqh students and moral aqidahs that use power points and digital teaching materials have not had an impact on learning achievement because they are not adjusted to the learning styles of students and are not accompanied by motivation from teachers and sometimes abusing ICT use for something which is not expected by the teacher. While the teacher of the Qur'an's Hadith and History of Islamic Culture, despite the lack of use of ICT in learning, is balanced by giving motivation when presenting material and ease of learning.